Twenty-Two Cents an Hour : Disability Rights and the Fight to End Subminimum Wages - Crandell, Doug (Book collections on Project MUSE., 2022)
"In 1938 the Fair Labor Standards Act authorized the use of subminimum wages for workers with disabilities. While some states have banned their use, it remains legal federally. The program known as 14(c) has a long history of poor oversight and abuse. While disability rights have grown in the United States, this issue lags decades behind"--